Meghalaya's nature-based tourism and visitors' environmentally conscious behaviour in response to climate change - kumar, paramjeet (Turizam, 2025)
This study explores the complex interactions that exist between travellers' understanding of climate change, environmentally conscious behaviour, and the experiences that result from these interactions within Meghalaya's nature-based tourism industry. Using a mixed-methods approach, information was gathered from a wide range of visitors who were visiting the area via structured questionnaires and in-depth interviews. Our research reveals a range of incentives, obstacles, and triggers influencing visitors' responsible behaviour, providing a more complex picture of their pro-environmental views and behaviours. Travellers' awareness of environmental issues becomes more important as a result of climate change, leading them to adopt more sustainable behaviours. The research reveals discernible trends of ecologically conscious behaviour across diverse population groups, providing insight into the possibility of customised treatments. Additionally, the study delves into the complex relationships that exist between visitors' increased environmental consciousness and the calibre of their experiences in nature. Studies show a mutually beneficial connection in which environmentally responsible decisions enhance visitors' overall enjoyment and sense of the genuineness of their experiences with Meghalaya's natural treasures. As we explore the implications for practice and policy, this research adds to the growing body of empirical research in the field of sustainable tourism and provides useful information for those involved in determining how nature-based tourism will develop in Meghalaya in the face of climate change.
Keywords: Meghalaya, climate change, nature-based tourism, tourist, environment.